Effect of aggregate type on moisture susceptibility of modified cold recycled mix asphalt: evaluation by mechanical tests and Surface Free Energy method (Fracture and Structural Integrity, 2020)
There are deficiencies associated with cold mix asphalts, specifically, cold recycled mix asphalts in comparison with hot mix asphalt or hot recycled mix asphalt such as higher moisture susceptibility. Moisture damage of asphalt mixtures is inversely related to the bond quality between aggregates and binder. In this study, Portland cement (PC) and acryl polymer (AP) additives were employed to improve this bond. The effectiveness of used additives in improving the moisture susceptibility of cold recycled mix asphalt was examined using Surface Free Energy (SFE) method. Indirect Tensile Strength test and Dynamic Modulus test were performed to validate SFE method results. Moreover, scanning electron microscope (SEM) images were obtained for better understanding of mixture's microstructure. Also, effect of using granite, limestone and recycled asphalt pavement (RAP) aggregates was evaluated. The findings showed that cement and acryl polymer additives improved resistance of different studied mixtures, specifically, cold recycled mix asphalt against moisture damage by improving the adhesion between aggregate and asphalt. Considering effect of aggregates on moisture susceptibility, limestone-mixtures had the highest resistance while the RAP-mixtures performed the worst among the three. Finally, it was shown that results of SFE method were compatible with the mechanical tests in predicting moisture damage.
Keywords: Cold recycling; Acryl polymer; Portland cement; Moisture susceptibility; Surface free energy